2011
DOI: 10.1007/s00198-011-1832-6
|View full text |Cite
|
Sign up to set email alerts
|

Vertebral body bone strength: the contribution of individual trabecular element morphology

Abstract: Microarchitectural measures of individual trabeculae that contribute to bone strength have been identified. In addition to the contribution of BV/TV, trabecular rod morphology increased the determination of AP strength by 57%, whereas measures of trabecular plate and rod morphology increased determination of SI strength by 13%. Decomposing vertebral body bone architecture into its constituent morphological elements shows that trabecular element morphology has specific functional roles to assist in maintaining … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…In line with previous studies [34], [35], HU resulted in marked deterioration in trabecular bone microarchitecture, as evidenced by decreased trabecular BMD, Tb.N, Tb.Th and BV/TV, and increased Tb.Sp. More importantly, increased trabecular SMI was also observed in HU rats, revealing a potentially dramatic reduction of trabeculae with plate-like structures [36]. Moreover, in accordance with previous findings [35], skeletal disuse by HU caused lower cortical bone thickness in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…In line with previous studies [34], [35], HU resulted in marked deterioration in trabecular bone microarchitecture, as evidenced by decreased trabecular BMD, Tb.N, Tb.Th and BV/TV, and increased Tb.Sp. More importantly, increased trabecular SMI was also observed in HU rats, revealing a potentially dramatic reduction of trabeculae with plate-like structures [36]. Moreover, in accordance with previous findings [35], skeletal disuse by HU caused lower cortical bone thickness in the present study.…”
Section: Discussionsupporting
confidence: 93%
“…Although there were no significant differences between cubic and cylindrical µFE models, the positions of the trabecular bone core should be identical. In experimental compression tests, trabecular bone cores extracted from vertebral bodies are often used (23,32). In our study, cubic and cylindrical µFE models were constructed to investigate if there were differences between the two models.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that the trabecular architecture of vertebral centrum could affect the mechanical properties of vertebral bone [22, 40]. The trabecular thickness (Tb.Th) and fracture strength of rat vertebrae were shown to have significantly decreased 2 months post-OVX, while trabecular formation and resorption surface area were increased [22].…”
Section: Discussionmentioning
confidence: 99%